Perbandingan Performansi Antara Differential Evolution dan Bat Algorithm pada Tuning PID Untuk Optimasi Kontrol Kecepatan Paralell Hybrid Electric Vehicle - Simson, Simson (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
In the last decade, there have been many means of transportation that use fuel oil (Internal Combustion Engine (ICE)). This has a serious impact on the environment due to the emission of pollutant gases. One solution is the use of a hybrid electric vehicle (HEV) as a substitute for vehicles that use ICE. One of the performance that must be owned by the HEV is to have a stable speed when driving. In this study, several methods used in the metaheuristic algorithm in the disturbance observer have the advantage of describing the inverse model of the plant without making a mathematical model. The test is carried out by comparing the two methods of the metaheuristic algorithm, namely Differential Evolution and Bat Algirthm. The simulation results show that the method used in this HEV is to maintain its speed, so according to the test results it shows that the Differential Evolution method is the best method for controlling the speed of the Parallel Hybrid Electric Vehicle.